Electron Microscopic Radioautographic Study on Protein Synthesis in Hepatocyte Mitochondria of Aging Mice - Tetsuji Nagata (The Scientific World Journal)
For the purpose of studying the aging changes of intramitochondrial protein synthesis in mouse hepatocytes, 10 groups of aging mice, each consisting of 3 individuals (total 30), from fetal day 19 to postnatal month 24, were injected during development with 3H-leucine, a protein precursor, sacrificed 1 h later, and the liver tissues processed for electron microscopic (EM) radioautography. On EM radioautograms obtained from each animal, the number of mitochondria, the number of labeled mitochondria, and the mitochondrial labeling index labeled with silver grains due to 3H-leucine showing protein synthesis in each mononucleate hepatocytes were counted and the averages in respective aging groups were compared. From the results, it was demonstrated that the numbers of mitochondria, the numbers of labeled mitochondria, and the labeling indices of intramitochondrial protein syntheses in mononucleate hepatocytes of mice at various ages from embryonic day 19 to postnatal month 24 increased and decreased due to development and aging of animals.